Present situation in Turkey regarding malnutrition in infants and preschool children - types of problems, magnitude of problems, location - Baysal, Ayşe (The Turkish Journal of Pediatrics, 1968)
No overall nutrition survey of the Turkish population has been carried out for the assessment of the nutritional status of various groups and few reports have been published concerning the prevalence of malnutrition among infants and preschool children. Findings of the reports available indicate that malnutrition is an important problem in child health. The type, magnitude and location of the problem: The infant and child mortality rate is very high, with an average 154 and 40 per 1000 for infants and toddlers (one to four years of age) respectively; 30 to 50 per cent of infants and children are below standard weight and height; average birth weight is comparable with those in the United States and Europe; retardation in growth starts after three months of age and reaches its highest degree at 18 to 24 months; among growth-retarded children, one to four per cent are brought to the hospital with signs of severe marasmus; the main secondary complications of malnutrition are gastroenteritis and pneumonia; most malnourished children die from secondary infections and these are listed as the cause of death; other signs of malnutrition are anemia and rickets; malnutrition is more common among the children of low socio-economic groups of the cities and villages; and the most important factors affecting malnutrition are ignorance, unavailability of high quality, low cost infant food mixtures and poor socio-economic conditions.